2007
DOI: 10.1007/s11746-007-1138-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deep‐Fat Frying on Phytosterol Content in Oils with Differing Fatty Acid Composition

Abstract: The objective of this study was to determine the fate of phytosterols in vegetable oils with varying fatty acid composition used for frying. High oleic sunflower (HOSun), corn (Corn), hydrogenated soybean (HSBO), expeller pressed soybean (ESBO), and expeller pressed lowlinolenic acid soybean oil (ELLSBO) were used for frying potato chips in a pilot plant-scale continuous fryer. The same oils, and regular soybean oil (SBO) were also used in intermittent batch frying of tortilla chips. Phytosterols were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…22,41,43 By comparing these works with the present work, it can be noted that a similar behavior related to the relative quantities of each compound was found in the seeds oils, with β-sitosterol as the compound found in the highest abundance. Alternatively, comparing the concentrations found in passion fruit seed oil with the other seed oils, the concentrations found in passion seed oil were about twice as high than Zhejiang pecan oil and Sacha inchi oil and, about 1.5, 2 and 5 times lower than soybean, sunflower and corn oils, respectively.…”
Section: Analysis Of Passion Fruit Seed Oils From Different Speciessupporting
confidence: 73%
See 1 more Smart Citation
“…22,41,43 By comparing these works with the present work, it can be noted that a similar behavior related to the relative quantities of each compound was found in the seeds oils, with β-sitosterol as the compound found in the highest abundance. Alternatively, comparing the concentrations found in passion fruit seed oil with the other seed oils, the concentrations found in passion seed oil were about twice as high than Zhejiang pecan oil and Sacha inchi oil and, about 1.5, 2 and 5 times lower than soybean, sunflower and corn oils, respectively.…”
Section: Analysis Of Passion Fruit Seed Oils From Different Speciessupporting
confidence: 73%
“…The extraction time decrease can be associated to the cavitation effects promoted by the use of ultrasonic radiation during the saponification step. 41 …”
Section: Ultrasound-assisted Saponification (Uas)mentioning
confidence: 99%
“…Given that the nuts analyzed here had more phytosterols than oil-roasted cashews, it would seem likely that the dry-roasting heat treatment was less harsh on phytosterol content than traditional oil-roasting. Although phytosterols have been recognized for their ability to reduce cholesterol levels in the human body, the levels found in the cashews do not qualify for an FDA approved health claim (Winkler, Warner, & Glynn, 2007). Pairwise differences determined by Tukey's HSD Phospholipids (PL) play a structural role in all cell membranes, but also act as secondary messengers in regulation in plant growth and stress adaptation (Xue, Chen, & Mei, 2009).…”
Section: Lipid Analysismentioning
confidence: 99%
“…Studies cited by Piironen et al, (2000) indicated that the contents of phytosterols in raw soybean oil vary between 2,290 and 4,490 µg.g -1 and between 2,210 and 3,280 µg.g -1 in refined soybean oil. This type of oil showed lower loss of phytosterols in a continuous frying system compared with corn and sunflower oils (Winkler et al, 2007).…”
Section: Chemical Structure and Properties Of Phytosterolsmentioning
confidence: 77%